Research competence accounting profession as a specialist business process management in processing industries - Rozhelyuk, Viktoriya (Skhid, 2015)
The article is the realization of research competence accountancy profession as a specialist business process management in processing industries. The main base for the study are research scientists to research the accounting profession as a specialist business process management in processing industries. When writing articles used methods: monographic (the study of scientific publications of scientists for the development of basic principles of formation of accounting in the processing industry), theoretical synthesis method (with a theoretical analysis of the basic job requirements, principles and requirements of operation chief accountant). Research results. The stages of requirements for the operation positions of chief accountant and financial director. The characteristic advantages of the profession. The author systematized the basic job requirements for the accountancy profession. Scientific novelty of research results is the main justification for the development of research results and formation vysokvalifikovanoho and competent accountant - expert in domestic processing industries. The practical significance of the study. The results in the paper is the basis for solving scientific and theoretical issues related to improving professional competence problems accountant.